Synthesis and structures of calcium and strontium 2,4-di-tert-butylphenolates and their reactivity towards the amine co-initiated ring-opening polymerisation of rac-lactide. - Clark, L; Deacon, G; Forsyth, C; Junk, P; Mountford, P; Townley, J; Wang, J (2013)
Calcium and strontium metals react with Hg(C6F5)2 and 2,4-di-tert-butylphenol (H-DBP) in tetrahydrofuran (THF) and 1,2-dimethoxyethane (DME) to give [Ca(DBP)2(THF)4] (1), [Ca2(DBP)4(DME)4(μ-DME)] (2), [Sr3(μ-DBP)6(THF)6] (3), and [Sr2(DBP)(μ-DBP)3(DME)3] (4). Compound 1 is a six coordinate trans-octahedral monomer, whereas in binuclear 2 two seven-coordinate Ca centres are bridged by a DME ligand. In 3 a central Sr is connected by three bridging DBP groups to each of two terminal Sr(THF)3 moieties, all metal atoms being six coordinate. Compound 4 has one six- and one seven-coordinate Sr, bridged by three DBP ligands, the former Sr also having a terminal DBP and a bidentate DME ligand and the latter two DME ligands. Complexes 2 and 4 act as ring-opening polymerisation (ROP) catalysts for the benzyl alcohol or benzylamine co-initiated ROP rac-lactide forming atactic alcohol- or amine-terminated polylactide H-[PLA]-XBn (X = O or NH) with reasonable control of molecular weight via an activated monomer propagation mechanism. Kinetic studies for BnNH2 found the unusual rate expression -d[LA]/dt = k(p(Ae))[2 or 4]0[rac-LA](2)[BnNH2]0(2.5) (k(p(Ca)) ≈ 1.7 ×k(p(Sr))). Preliminary studies suggest that [Y(DBP)3(THF)2] also catalyses amine or alcohol co-initiated ROP by an activated monomer mechanism without loss of a phenoxide ligand.